Exercise as an adjunctive therapy for patients on maintenance hemodiafiltration - Jessica L. F. Andrade; Ayden T. Heitmann; Miguel K. Rodrigues; Dave K. Marchand; Adelson M. Rodrigues; Bruno P. Biluca; Rene Freitas; Thiago Reis; Miguel A. Goes; Mayron F. Oliveira (Kidney Research and Clinical Practice, 2025)
Background Fatigue and sedentarism are common in kidney disease and dialysis treatment. Although hemodiafiltration effectively removes solutes and improves mortality, the influence of exercise as an adjunct therapy on maintenance hemodiafiltration programs remains understudied. Methods A multicenter 6-month study was assessed comparing individuals with chronic kidney disease enrolled in exercise training (exercise group) during dialysis (intradialytic vs. interdialytic) compared to usual care (control group). Physical tests included a YMCA step test for endurance, handgrip, and one-repetition maximum for muscle strength. Single-pool, standard, and equilibrated Kt/Vurea were surrogates for hemodiafiltration adequacy. Results Eighty-nine patients (54 ± 15 years) and 33 control patients (60 ± 17 years) underwent the exercise protocol. The mean disease vintage was 108 ± 84 and 132 ± 108 months, respectively, while the dialysis vintage was 60 ± 42 and 60 ± 36 months. Control-group Kt/Vurea showed improvement from baseline to month 6 (single-pool, 1.18 ± 0.03 to 1.30 ± 0.04; standard, 1.94 ± 0.04 to 2.09 ± 0.04; equilibrated, 1.09 ± 0.03 to 1.21 ± 0.02; p < 0.001). However, exercise-group Kt/Vurea showed a comparatively greater improvement between the baseline and month 6 (single pool, 1.19 ± 0.05 to 1.47 ± 0.04; standard, 1.99 ± 0.03 to 2.15 ± 0.03; equilibrated, 1.08 ± 0.03 to 1.24 ± 0.03; p < 0.001). The exercise group had a statistically significant increase in the handgrip test (279.5 ± 78.5 N to 295.2 ± 76.5 N, p < 0.01) and fat-free mass (13.9 ± 2.8 kg/m2 to 14.4 ± 2.7 kg/m2, p < 0.01). There were no statistically significant differences between the interdialytic and intradialytic groups in dialysis adequacy and exercise variables. Conclusion Supervised exercise for maintenance hemodiafiltration patients was associated with improvements in dialysis efficiency/performance outcomes. The results support exercise as an adjunct therapy for hemodiafiltration patients whether conducted during the intradialytic or interdialytic period.